A REVIEW OF BENZOPYRAN DERIVATIVES IN PHARMACOTHERAPY OF BREAST CANCER - Piyush, Kumar; Kuldeep, Singh; Md. Azizur, Rahman; Misbahul, Hasan Syed; Pranay, Wal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
One of the naturally occurring compounds containing oxygen moiety is benzopyran. Depending on its substitution pattern, different biological effects are shown. The benzopyran ring system is present in many natural products (such as genistein, hesperidin, and warfarin) as well as synthetic products. It displays pharmacological properties such as antitumor, anti-HIV, antimicrobials, anti-inflammatory, and anticoagulants. The sufficient literature support and the fact that benzopyran has potential as a pharmacophore particularly as anti-breast cancer, etc, current research seemed pertinent keeping in view the mechanism of anti-breast cancer activity. Therefore, the objective of this review is to focus on important benzopyran analogs with anti-breast cancer activity and highlight their mechanisms of action.